Reaching Inaccessible Communities: Demonstration of Community-Based Solid Waste Management Sub-System in Metro Manila, Philippines - Constantino, Guinevere S.; Luna, Kristine Ann M.; Toleza, Anne Louise T.; Medina, Reynaldo R. (International Journal of Integrated Engineering, 2025)
In Metro Manila, Philippines, numerous communities remain inaccessible to municipal waste collection services due to narrow streets and alleys. This often leads to improper waste disposal, including non-segregation and dumping in waterways. To address this, a community-based solid waste management sub-system (CBSWMS) was demonstrated in 78 selected barangays across Manila, Pasay, Taguig, Pasig, and Pateros, utilizing the Act-Learn principle. The CBSWMS comprised three core components: (1) establishing a community-led SWM sub-system in inaccessible areas, facilitated by Women’s Groups (WGs) as barangay SWM partners; (2) implementing a three-tiered sub-system promoting waste segregation and diversion before final disposal; and (3) providing enabling mechanisms for effective implementation. Demonstration results indicate that sustainability mechanisms for WGs, including diverse income sources and gender-mainstreaming strategies, are crucial. Furthermore, an increased focus on segregation-at-source and adequate SWM resources (tools, equipment, and dedicated sorting/recovery spaces) are vital for the sub-system's success and for increasing waste diversion rates.